Anti-IL-5 and IL-5Ra: Efficacy and Safety of New Therapeutic Strategies in Severe Uncontrolled Asthma. (5th November 2018) - Bagnasco, Diego; Caminati, Marco; Ferrando, Matteo; Aloè, Teresita; Testino, Elisa; Canonica, Giorgio Walter; Passalacqua, Giovanni
Abstract : The current developments of the new biological drugs targeting interleukin 5 (IL-5) and IL-5 receptor allowed to expand the treatment options for severe hypereosinophilic asthma. Clinicians will then be able to choose between antibodies targeting either circulating IL-5 or its receptor expressed on eosinophils and basophils. The available clinical trials consistently reported favorable results about the reduction of exacerbations rate, improvement in quality of life, and sparing of the systemic steroid use, with a favorable safety profile. Two of these new drugs are administered subcutaneously, mepolizumab every 4 weeks and benralizumab every 8 weeks, whereas reslizumab is given intravenously monthly on a weigh-based dose. In the future, the research actions will be involved in the identification of a single biomarker or multiple biomarkers for the optimal choice of biological agents to be properly prescribed.